Więzi organizacyjne w strukturach administracji publicznej jako przedmiot regulacji prawa administracyjnego - Izdebski, Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Public administration from the subjective point of view is a set of complex organizational units. The possibility of proper implementation of public tasks by individual entities of public administration depends mostly on the organizational efficiency of public administration offices - human teams supporting public administration bodies in exercising competences. The efficiency of operations of individual organizational units, the public administration offices, is conditioned by the quality of organizational ties present in them. Organizational ties in organizational units of public administration are, to a large extent, formalized. It results from the public-law nature of public administration activities and established administration practices adopted in a given country. The current increase in requirements as to the quality, efficiency and openness of public administration activities means that the correct formation of organizational ties in each organizational unit of public administration can have a significant impact on the level of implementation of public tasks. A high level of formalization of the basis of organizational ties in public administration should not be treated as an obstacle to the effective shaping of modern administrative structures based on solutions in the private sector. The determined level of formalization of the structure of organizational units of public administration is to provide those values that are fundamental for the operation of public administration entities: the rule of law, equality before the law. The formation of organizational ties within the framework of the formalization of public administration structures should be a compromise between the necessary elements giving the basis for applying uniform principles to the administrated, citizens and solutions aiming to ensure professionalisation and to improve the quality of public administration organizational units.